Asymmetries in the Coordinated Direct Investment Survey : What Lies Behind? - Angulo, Emma (IMF Working Papers; Working Paper ;, 2017)
This paper analyzes asymmetries in direct investment positions reported in the Coordinated Direct Investment Survey (CDIS) following a top down approach. First, it examines asymmetries at global level; second, it examines asymmetries between CDIS reported and derived data for individual economies; and third, the paper analyzes data at bilateral economy level. Then, the paper explores seven main reasons for asymmetries, including those arising even when economies follow international standards. Finally, the paper includes a section on addressing bilateral asymmetries and concludes with specific planned actions to reduce asymmetries, including initiatives led by international organizations.